Extrapolating Empirical Models of Satellite‐Observed Global Mean Sea Level to Estimate Future Sea Level Change - R. S. Nerem; T. Frederikse; B. D. Hamlington (Earth's Future, 2022)
Abstract We estimate a quadratic model of climate‐driven global mean sea level (GMSL) change based on the satellite altimetry record (1993–2020), including a rigorous assessment of the errors in the quadratic coefficients. We then extrapolate this model 30 years into the future to 2050 and compute the 90% confidence interval. We find GMSL rise in 2050 relative to 2020 will be 16.4 cm higher, with an uncertainty range of 11.3–21.4 cm. This prediction agrees within uncertainties with IPCC SROCC and AR6 sea level projections. In addition, a hindcast extrapolation prior to 1993 agrees well with the tide gauge record of GMSL change over the 2nd half of the 20th century. We believe this shows the value of short‐term observationally driven extrapolations as an additional tool for predicting future sea level change.